A containment based distributed finite-time controller for bounded voltage regulation & proportionate current sharing in DC microgrids. (15th October 2018) - Sahoo, Subham; Pullaguram, Deepak; Mishra, Sukumar; Wu, Jianzhong; Senroy, Nilanjan
Highlights: Distributed secondary energy management of DC microgrids is developed. Stable performance during communication delay and link failure is ensured. Reverse droop methodology is used to enhance the controller's dynamic performance. Maximum allowable transmission delay is determined to observe system's stability. Abstract: As link failure in a centralized network results into unstable behavior, the distributed control mechanism is often employed since the reliability and stability is enhanced by communicating with the neighbors thereby reducing the infrastructural cost required for communication. However, such compromised spanning loosely connected networks may sometimes lead to slow convergence or may even go unstable. Under such circumstances, it is essential to incorporate fast convergence speed using limited information for each controller to enhance operational reliability. Hence, this paper proposes a distributed secondary controller for each unit comprising of PV & batteries to achieve average regulation within predefined bounds and proportionate current sharing between units in finite time for DC microgrids for uniform energy management in each unit. To conform to the containment control philosophy, the followers converge to the leaders' command in finite-time. To alleviate the dynamic performance in a significantly resistive network, a reverse droop methodology is adopted concurrently to the proposed distributed secondary controller thereby eliminating the issue of cascaded control loops. A Lyapunov based analysis is carried out to analyze its stability for varying control parameters alongwith a bode plot analysis to determine its stability margins. In addition to this, a time-delay analysis is carried out to calculate the maximum transmission delay that the controllers can withstand to maintain stability. To test the robustness of the designed controller, it is simulated for disturbances such as load change, communication delay, converter failure, link failure between leader-follower & two followers. Moreover, the real-time simulation using software-in-loop of the modeled system is also done to test the efficacy of the proposed strategy.